Kein Etwas, aber auch nicht ein Nichts Religionsphilosophische Untersuchungen zu Ludwig Wittgenstein, Jürgen Habermas und Charles Taylor - Schneider, Hans Julius (Mohr Siebeck, 2025)
Hans Julius Schneider applies Wittgensteins Philosophy of Psychology as a means to improve our understanding of religious language. He shows that in both fields it is necessary to distinguish two levels of meanings. As in psychology speaking about pain is not on the same level as speaking about the nervous system, so in religion speaking about God is categorically different from speaking about Socrates.
PublicationDate: 20250630
Keywords: Religiöse Erfahrung -- Nichtvermögensschäden -- Arabic Diatessaron -- interreligiöse Kommunikation -- Erfüllungszitat -- Gottessohn -- Davidssohn -- Lobrede -- Artikulationsformen -- Religionsphilosophie -- Erkenntnistheorie